Cross-level group density interactions on mental health for cultural, but not economic, components of social class. (March 2022) - Saville, Christopher W N; Mann, Robin
Abstract: Background: The ethnic density literature links mental health to ethnic minority status in one's neighbourhood. This design has also been applied to other identities, including sexual and political minorities, but surprisingly little attention has been paid to class-based identities. We use a Bourdieusian framework to examine whether a 'class density' association with mental health can be found for economic capital – people's material assets – and cultural capital – symbolic signifiers of class, such as tastes and interests. Methods: Multi-level regression with post-stratification was used to make area-level estimates of cultural and economic capital for each middle super output area in Wales, using data from the National Survey for Wales 2017/18 (N = 11, 381). These estimates were linked to independent individual-level data from the 2018/19 edition of the same survey (N = 4058) and mixed effects models containing individual-level capital, area-level capital, and their interaction were fitted, predicting whether respondents reported a mental health problem. Models were fitted unadjusted, adjusted for age and gender; for the other form of capital on the individual and area levels; and for the other capital's cross-level interaction. Multiple imputation was used to account for missing data. Results: For cultural capital, a cross-level interaction was found where area-level cultural capital was protective in respondents reporting higher levels of individual-level cultural capital, but a risk factor for mental health problems in those with low individual-level cultural capital (odds ratio = 0.83, CI95%  = 0.75-0.93). No such relationship was found for economic capital (odds ratio = 0.96, CI95%  = 0.88–1.06). These results remained robust in adjusted models. Conclusions: The presence of a class density association with mental health for cultural capital but not economic capital suggests that symbolic signifiers of class, more than material aspects, activate class identities and drive group density phenomena. There are implications for planning policy, mental health, and political leadership. Highlights: Living in an area where one's group is in the minority is associated with poorer mental health. Most commonly shown for ethnic groups, but evidence this also applies to social class. We examined whether this was driven by economic or cultural aspects of class. Group density association with mental health found for cultural but not economic aspects of class.